Post-graduate student performance in ‘supervised in-class’ vs. ‘unsupervised online’ multiple choice tests: implications for cheating and test security - Ladyshewsky, Rick (Routledge, 2014)
This research explores differences in multiple choice test (MCT) scores in a cohort of post-graduate students enrolled in a management and leadership course. A total of 250 students completed the MCT in either a supervised in-class paper and pencil test or an unsupervised online test. The only statistically significant difference between the nine test scores was for one test where the students scored significantly lower in the unsupervised online test. There was no increase in mean test scores over time and the mean test scores for the unsupervised online test were not significantly higher than the mean test scores for the supervised in-class test. The study suggests that unsupervised online MCTs can be a viable tool for assessing knowledge in post-graduate students provided they meet best practice standards for online assessment. Concerns about increased cheating in unsupervised online testing are not supported.